Patient-Centered Communication Behaviors That Correlate With Higher Patient Satisfaction Scores. (September 2018) - Finefrock, Doug; Patel, Sridhar; Zodda, David; Nyirenda, Themba; Nierenberg, Richard; Feldman, Joseph; Ogedegbe, Chinwe
Background: With increased emphasis on improving the patient experience, clinicians are being asked to improve their patient-centered communication behaviors to improve patient satisfaction (PS) scores. Local Problem: The relationship between clinician communication behaviors and PS is poorly studied in the emergency department (ED) setting. The purpose of this study was to identify whether specific communication behaviors correlate with higher PS scores in the ED setting. Methods: During a quality improvement project, we performed 191 bedside observations of ED clinicians during their initial interaction with patients and recorded the frequency of 8 positive communication behaviors as defined by the PatientSET tool. Interventions: The frequency of use of the PatientSET communication behaviors was compared between known high performers in Press Ganey PS scores versus low performers. Results: Being a high Press Ganey performer was associated with a significantly higher frequency of performance in 6 of the 8 PatientSET communication behaviors. Conclusions: Positive communication behaviors such as those in the PatientSET tool occurred more frequently in ED clinicians with higher PS scores.